Diabetic Bone Disease Basic and Translational Research and Clinical Applications - Lecka-Czernik, Beata; Fowlkes, John L. (Springer International Publishing : Imprint: Springer, 2016)
Providing the most up-to-date research and current clinical knowledge of diabetic bone disease and the challenges still facing the research and clinical care communities, this book unites insights from endocrinology to orthopedics to create a truly unique text. The first part covers clinical and pre-clinical applications and research. The first two chapters present the clinical and epidemiological data about diabetic bone disease, evaluated and reviewed for type 1 and type 2, respectively. This is followed by discussions of how the propensity to fracture in diabetic bone disease can impact fracture risk assessments and how it can be adjusted for using current clinically relevant fracture risk models. A comprehensive overview of orthopedic complications observed in diabetes is next, as well as a focus on the consequences of diabetes on periodontal disease. Other topics include the utility of skeletal biomarkers in assessing diabetic bone disease, how drugs used to treat diabetes may also have skeletal consequences, and the possibility that diabetes may fundamentally impact early progenitor cells of various bone lineages and thus globally impact bone. The second part covers biomechanics and bone quality in diabetes: how diabetes ultimately may impact the architecture, integrity, and quality of bone. Utilizing the expertise of top researchers and clinicians in diabetic bone disease in one comprehensive text, this volume will be a useful and thought-provoking resource for endocrinologists and orthopedic surgeons alike.